2016
DOI: 10.1055/s-0042-107669
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Issues in Conducting Pilot Trials in Chronic Pain as Randomized, Double-blind, Placebo-controlled Studies

Abstract: Both studies were associated with methodological issues, including populations with different disease entities, small sample sizes, use of concomitant analgesics, and possible placebo effect that may have led to the failure to differentiate between tapentadol ER and placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…No difference was observed between placebo and treatment groups for the patient global impression of change and for responders at ≥30% and ≥50% pain reduction 58. These negative and disappointing findings have been ascribed to study design factors such as study underpower, heterogeneity of patients contributed in small numbers by 33 study centers in Japan, potential genetic factors and high numbers of uncontrolled concurrent medications; the authors reported also an unusually high placebo response probably due to large expectations generated in the patients from the 2:1 (treatment:placebo) enrollment design 58. Recently, in the context of a complex therapy including gabapentin 1800 mg/day, oxacarbazepine 600 mg/day and amytriptiline 20 mg/day, tapentadol 500 mg/day failed to relieve pain in a 68-year-old patient suffering from trigeminal PHN 76…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…No difference was observed between placebo and treatment groups for the patient global impression of change and for responders at ≥30% and ≥50% pain reduction 58. These negative and disappointing findings have been ascribed to study design factors such as study underpower, heterogeneity of patients contributed in small numbers by 33 study centers in Japan, potential genetic factors and high numbers of uncontrolled concurrent medications; the authors reported also an unusually high placebo response probably due to large expectations generated in the patients from the 2:1 (treatment:placebo) enrollment design 58. Recently, in the context of a complex therapy including gabapentin 1800 mg/day, oxacarbazepine 600 mg/day and amytriptiline 20 mg/day, tapentadol 500 mg/day failed to relieve pain in a 68-year-old patient suffering from trigeminal PHN 76…”
Section: Introductionmentioning
confidence: 82%
“…In a subset of 13 PHN patients, tapentadol PR was not superior to placebo 58. Pain Numerical Rating Scale (NRS) declined from pretreatment to treatment week 12 from 7.0±1.4 to 5.0±2.9 in the placebo group and from 6.7±0.9 to 4.5±2.3 in the tapentadol group (mean reduction 2.0±2.4 and 2.2±2.2) 58. No difference was observed between placebo and treatment groups for the patient global impression of change and for responders at ≥30% and ≥50% pain reduction 58.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations